Adherence to the bowel cleansing regimen for pan-enteric capsule endoscopy in patients with suspected Crohn's disease and factors affecting the image quality. (3rd April 2022) - Brodersen, Jacob Broder; Andersen, Karina Winther; Jensen, Michael Dam
Abstract: Objective: Pan-enteric capsule endoscopy (CE) is an attractive diagnostic approach in patients examined for Crohn's disease (CD). The aim of this study was to examine the adherence to the recommended bowel cleansing regimen and determine clinical factors affecting the image quality. Methods: In a prospective blinded trial, patients with suspected CD were examined with the PillCam Crohn's capsule after bowel preparation with 2 + 2 L of polyethylene glycol (PEG) and sodium phosphate booster. The image quality was graded on a four-point scale. A good or excellent image quality defined a diagnostic procedure. Results: Fifty-nine patients participated. The mean volume of PEG was 2.5 L (CI 2.3–2.8). Ten patients (17%) were able to drink all 4 L of PEG, and 44 patients (75%) ingested ≥2 L. The image quality was poor, fair, good or excellent in 0%, 29.3%, 29.3% and 41.4%, respectively. The mean volume of PEG was 1.9 L (CI 1.4–2.4), 2.2 L (CI 1.8–2.7) and 3.2 L (CI 2.8–3.5) in patients with a fair, good or excellent image quality ( p < .001). In a regression analysis, only the volume of PEG was associated with the obtained image quality ( r s =0.52; p < .001). The diagnostic yield was equal in patients with a diagnostic or non-diagnostic procedure (43.9% and 47.1%, respectively). Conclusions: In patients examined with pan-enteric CE for suspected CD, the volume of PEG is the major factor affecting the image quality. Although few patients are able to ingest the recommended volume, the diagnostic yield is not affected.